Kerusakan Tanaman Cabai Akibat Penyakit Virus Di Desa Waimital Kecamatan Kairatu - G.N.C Tuhumury; Handry R.D Amanupunyo (Agrologia, 2013)
One of the constraints faced by farmers in the cultivation of chili in Transmigration Areas District Kairatu Waimital Village is a disease caused by virus. This study was conducted to know the types of viruses that attack chili plants and how worse the damage intensity. The method used was a survey method directly in the field. Farmer decision-sample and sample plots was done using a random sampling technique. The data collected is the damage intensity of chili plants and the cause, the condition of the area/crop cultivation techniques, and rainfall data taken from Meteorology station (BMG). The results showed that the disease that attacks the chili plants in the Waimital village is a yellow virus and curl virus disease, with intensity of damage of 10.16% and 32.17% classified as mild and moderate, respectively.